2018
DOI: 10.1136/bmjopen-2017-019143
|View full text |Cite
|
Sign up to set email alerts
|

Does physiological distribution of blood parameters in children depend on socioeconomic status? Results of a German cross-sectional study

Abstract: ObjectivesIn the present study, we examined the relation between socioeconomic status (SES) and the physiological distribution of iron-related blood parameters.DesignThis is a cross-sectional analysis of longitudinal population-based cohort study.SettingBased on a sample of healthy participants from a German research centre, various blood parameters and values of clinical examinations and questionnaires were collected.ParticipantsA total of 1206 healthy volunteers aged 2.5 to 19 years, one child per family ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Results from the German KiGGS study suggest that children and adolescents with low SES are half as likely as those with high SES to have good general health; they were significantly more affected by psychological and behavioral difficulties [11]. Exposures to stress could influence physiological and psychological processes, resulting, for example, in cell/molecular damage [36], poorer emotional health [12], and health behavior, like reduced physical activity and poor diet [13]. Moreover, exposure to early life stress could influence both the hypothalamic-pituitary-gonadal and hypothalamic-pituitary-adrenal axes and thus provide a link to advanced pubertal maturation [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results from the German KiGGS study suggest that children and adolescents with low SES are half as likely as those with high SES to have good general health; they were significantly more affected by psychological and behavioral difficulties [11]. Exposures to stress could influence physiological and psychological processes, resulting, for example, in cell/molecular damage [36], poorer emotional health [12], and health behavior, like reduced physical activity and poor diet [13]. Moreover, exposure to early life stress could influence both the hypothalamic-pituitary-gonadal and hypothalamic-pituitary-adrenal axes and thus provide a link to advanced pubertal maturation [40].…”
Section: Discussionmentioning
confidence: 99%
“…The SES of children was assessed at their first visit recorded in the data using the “Winkler-Stolzenberg-Index” [9, 12, 13, 23]. This index comprises 3 scales measuring parental education, occupational status and household equivalized disposable income (for more information see [23]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that children growing up in families with a lower SES have a higher body mass index (BMI) [ 9 , 10 , 11 , 12 ], report more behavioral problems [ 13 , 14 , 15 ], more psychosomatic symptoms [ 16 ], a lower quality of life [ 17 , 18 ], less healthy nutrition [ 19 , 20 ], less physical activity [ 16 , 21 , 22 , 23 ], a higher media consumption [ 22 , 23 , 24 , 25 , 26 ], and experience more critical life events than children growing up in families with a higher SES [ 27 ]. There is further evidence of associations between SES and laboratory parameters, e.g., serum lipid levels [ 28 ] and hemoglobin [ 29 ]. Some studies reported smaller associations between SES and health outcomes in adolescents compared to children or adults [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%